Lighting a candle, or cursing the darkness? Delivering a climate friendly anaesthetic. (18th November 2021) - Skowno, Justin; Weatherall, Andrew
Abstract : With up to 7% of national emissions coming from health care in industrial nations, and volatile anaesthetics and nitrous oxide being particularly effective greenhouse gases, anaesthetists can potentially reduce their medical carbon footprint substantially. Operating theatres create 25% of hospital waste, and there are many other avenues for 'greening' in the perioperative environment, including recycling and avoiding unnecessary operations. However, it is vital to understand how to produce a real change in practice that continues into the future and is normalised. Health‐care choices we make in 2021 cannot be allowed to lead to a climate catastrophe in 2050.